Geographical and socioeconomic disparities in opioid access in Mexico, 2015-19: a retrospective analysis of surveillance data - David Goodman-Meza, MD; Joseph Friedman, MPH; Mariah M Kalmin, PhD; Emmanuel Aguilar-Posada, MPH; Marissa J Seamans, PhD; Sara Velazquez-Moreno, JD; Clara Fleiz, PhD; Michael Shin, ProfPhD; Jaime Arredondo-Sanchez, PhD; Steffanie A Strathdee, ProfPhD; Steve Shoptaw, ProfPhD (Elsevier, 2021)
Summary: Background: In 2015, Mexico implemented regulatory changes and an electronic system to improve access to prescription opioids. We aimed to investigate trends in opioid dispensing after the implementation of these changes and assess how opioid dispensing varied geographically and by socioeconomic status. Methods: In this retrospective analysis of prescription medication surveillance data, we analysed dispensing data for group 1 medications (all opioids, including morphine, methadone, hydromorphone, oxycodone, tapentadol, fentanyl, sufentanil, and remifentanil) obtained from the Federal Commission for the Protection against Sanitary Risk database for 32 states and six large metropolitan areas in Mexico. We calculated crude annual opioid prescriptions per 10 000 people at the national, state, and municipal levels. Adapting methods from the report of the Lancet Commission on Palliative Care and Pain Relief, we calculated the need for palliative opioids by state, and then assessed the observed opioid dispensing rates as a percentage of expected need by geographical socioeconomic status. Within the six major metropolitan areas, we mapped the geocoded location of opioid prescriptions and assessed the association between opioid dispensing and socioeconomic status as well as the association between opioid dispensing and time to US border crossing for areas on the US-Mexico border. Findings: Between June 25, 2015, and Oct 7, 2019, opioid dispensing rates increased by an average of 13% (95% CI 6·8-19·6) per quarter (3 months). The overall national opioid dispensing rate during the study period was 26·3 prescriptions per 10 000 inhabitants. States with a higher socioeconomic status had higher opioid dispensing rates than states with lower socioeconomic status (rate ratio [RR] 1·88, 95% CI 1·33-2·58, p=0·00016) after controlling for the estimated opioid requirement per state, the presence of methadone clinics, and the presence of tertiary hospitals and cancer centres. The same association between opioid dispensing and socioeconomic status was observed in the metropolitan areas, and in those metropolitan areas on the US-Mexico border a 20% decrease (RR 0·80, 95% CI 0·75-0·86) in opioid dispensation was observed per each SD increase (SD 17·1 min) in travel time to the border. Interpretation: Measures introduced by the Mexican federal Government to increase opioid access for patients with palliative care needs were only marginally successful in raising opioid prescription rates. Opioid access should be improved for patients with palliative care needs who live in geographical areas of lower socioeconomic status. Funding: US National Institutes of Health.